2014
DOI: 10.1016/j.chemosphere.2013.09.043
|View full text |Cite
|
Sign up to set email alerts
|

Atrazine leaching from biochar-amended soils

Abstract: The herbicide atrazine is used extensively throughout the United States for weed control, and is a widespread ground water and surface water contaminant. Biochar has been shown to strongly sorb organic compounds, and could provide a way to reduce atrazine leaching. Using lab and field experiments, we studied how biochar impacts atrazine leaching under increasingly heterogeneous soil conditions. Lab-scale soil columns dosed with biochar, atrazine, and simulated rain demonstrated that biochar application does re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
43
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(48 citation statements)
references
References 52 publications
(38 reference statements)
2
43
0
3
Order By: Relevance
“…In addition, the amount of fomesafen leached from the columns was conversely related with the amount of biochar added (Pearson correlation test: r > 0.985, p < 0.05). These results agree with previous observations of other chemicals . Si et al observed that a significant decreased in isoproturon leaching form 3 soils amended with different amounts of charcoal resulted from the larger adsorption capacity of charcoal for isoproturon.…”
Section: Results and Disscussionsupporting
confidence: 92%
“…In addition, the amount of fomesafen leached from the columns was conversely related with the amount of biochar added (Pearson correlation test: r > 0.985, p < 0.05). These results agree with previous observations of other chemicals . Si et al observed that a significant decreased in isoproturon leaching form 3 soils amended with different amounts of charcoal resulted from the larger adsorption capacity of charcoal for isoproturon.…”
Section: Results and Disscussionsupporting
confidence: 92%
“…Most of the available studies on nitrate leaching, however, have been conducted under a small range of soil textural classes, primarily on coarse‐textured soils, which are most susceptible to nitrate leaching. In general, biochar can be most effective for improving soil properties and productivity in coarse‐textured soils, low organic matter soils, and soils with reduced aggregate stability (Delwiche et al, 2014; Abrol et al, 2016; Blanco‐Canqui, 2017). Time after biochar application can also affect biochar performance.…”
Section: Biochar Amendment and Nutrient Leaching From Soilmentioning
confidence: 99%
“…The strong sorption of pesticides by biochar not only reduces pesticide losses through leaching but also reduces their losses through other pathways such as volatilization and erosion. For example, Delwiche et al (2014) conducted laboratory and field experiments to determine pine chip biochar impacts on atrazine leaching and found that biochar applied at 10 Mg ha −1 reduced cumulative atrazine leaching by 52% in soil columns. Biochar has been used in filtration systems to remove organic pollutants because of its high potential to adsorb toxic organic compounds (Miles et al, 2016).…”
Section: Pesticide Lossesmentioning
confidence: 99%
“…[43][44][45] These studies suggested that the decrease in pesticide leaching in amended soils was due to the increased sorption and decreased desorption. [43][44][45] These studies suggested that the decrease in pesticide leaching in amended soils was due to the increased sorption and decreased desorption.…”
Section: Inuence Of Biochar On the Leaching Of Bpa And Ee2mentioning
confidence: 99%